New methods to quantify an individual's scientific research output based on h-index and various factors - Zhao, Weifan; Liu, Wenjun; Zhang, Ruiyu (Qualitative and Quantitative Methods in Libraries, 2017)
Hirsch proposed h-index in 2005. To overcome some limitations of h-index in practical application, many scholars have proposed a series of derivative indexes. So far, derivative indexes designed by the scholars are mostly based on the citations and total number of papers. Although they are simple to use, they have certain oneness on the data source. To overcome this situation, two methods are used in this paper to analyze various factors. Firstly, we use the principal component analysis method to analyze original data such as the total number of papers, citation and so on, and then draw a comprehensive evaluation result of Z to quantify scientific research output, which avoid the oneness on the factor. Then, based on the "Gold priority" rule and h a - index proposed by Xu, we introduce a new comprehensive scientific research evaluation index, named as h f  - index, to enhance the degree of differentiation and sensitivity of h-index. For two methods above, examples are given respectively.